Subacute Cardiomyopathy Due to Statin Treatment: Can It Be True?—Case Report and Literature Review - Camelia Mihaela Georgescu; Ioana Butnariu; Cătălina Raluca Cojocea; Andreea Taisia Tiron; Daniela-Nicoleta Anghel; Iulia Ana-Maria Mitrică; Vlad-Iulian Lăptoiu; Adriana Bidea; Dana Antonescu-Ghelmez; Sorin Tuță; Florian Antonescu (Life)
Background and Clinical Significance: Statins are a widely used drug class associated with a plethora of muscular side effects ranging from the subclinical elevation of creatine kinase to fulminant rhabdomyolysis. Cardiac myopathy secondary to statin treatment is rare and was recently reported as a part of statin-induced necrotizing autoimmune myopathy (SINAM). Its occurrence outside of this context is still debated. Case Presentation: We present the case of a 60-year-old male who developed atorvastatin-induced rhabdomyolysis, without associated hydroxymethyl glutaryl coenzyme A reductase (HMGCR) antibodies, with clinical findings of cardiac failure and severe ECG anomalies. The symptoms slowly regressed with statin withdrawal, and the patient made a full recovery. We discuss the recently proposed statin-associated cardiomyopathy (SACM) and the possible mechanisms. We compare our case to the three other cases of statin-induced cardiac myositis found in the literature. Conclusions: We believe that in vulnerable patients, as was our case, statins can determine significant subacute cardiac toxicity. This would seem to occur in the context of severe skeletal muscle injury, probably due to higher metabolic resistance on the part of the myocardium. Also, the available evidence suggests myocardial involvement should be actively investigated in SINAM patients, preferably by cardiac MRI.